Effect of Non-Surgical Periodontal Therapy on Interleukin-33 and Interleukin-1β Levels in Sever Chronic Periodontitis Patients - Abdurahman AL Slama (Khalij-Libya Journal of Dental and Medical Research, 2024)
Aims. First, to determine the short-term effect of scaling and root planing on IL-33 levels in gingival crevicular fluid from patients with chronic periodontitis and compare these levels with those of IL-1β cytokine. Second, to establish the correlation between each of the clinical parameters and IL-1β levels with IL-33 levels in gingival crevicular fluid prior to and after periodontal treatment. Methods. A total of forty subjects, 20 with moderate to severe chronic periodontitis (study group) and 20 subjects with healthy gingiva (control group) were selectively collected for contribution in the present study. The chronic periodontitis patients (study group) received initial periodontal therapy (SRP). The periodontal clinical parameters including (PI, GI, BOP, PD and ALL) were measured and gingival crevicular fluids (GCF) were collected at baseline and four weeks after therapy for study group and at baseline for control group. Levels of interleukin-1β and interleukin-33 were measured using enzyme-linked immunosorbent assay kits. Results. There were statistically significant differences between the mean values of GI, PI, BOP, PD and ALL at baseline and after SRP in the study group (P < 0.001). The respective IL-β and IL-33 levels are significantly dropped from baseline to four weeks after (SRP) (96.26 ng/ml versus 33.1 ng/ml ,P=0.0001) for IL-β and (5.99 ng/ml versus 4.73 ng/ml ,P=0.0001) for IL-33. There was no significant correlation between all of the clinical parameters and interleukins levels in GCF except the significant correlation between interleukin-1β and bleeding index at 4 weeks after SRP (r=-0.448 & p=0. 048). Conclusion. Scaling and root planing (SRP) is the mainstay of treatment of periodontal diseases as SRP was effective in improving clinical parameters in patients with chronic periodontitis. This improvement was accompanied by a significant decrease in the levels of the proinflammatory cytokines IL-1β and IL-33 in GCF. IL-33 could be used as a potential diagnostic marker for periodontal disease activity in gingival crevicular fluid.